An examination of recent federal and philanthropic funding for child welfare research in the United States. (May 2023) - Simon, June; Hong, Jeeyeon; Pecora, Peter J.; Cloepfil, Geoffrey; Gillespie, Troy; Parker, Elizabeth; Klein, Reed; Garcia, Thalia; Hardy, Mariah
Highlights: This study identified the dollar value and research topics of federal and philanthropic grants made for child welfare research in a recent five-year period (2014–2018). More than $1 billion in child welfare research grants were identified and examined. Federal funding totaled $977 million and appeared to emphasize research related to evidence-based services and programs; child and youth behavioral health; behavioral health treatment; parent training and coaching; permanency planning and services; staff training; trauma-informed services; child developmental health; culturally competent services; case management; substance abuse treatment; birthparent services; systems reform and integration; implementation science and implementation evaluation; and adoption. Multi-state foundations funded $51 million in child welfare research, which appeared to emphasize mapping data related to child well-being; needs and services for adolescents ages 14–17 and young adults ages 18–25; independent living/transition services; education services; child and youth behavioral health; employment training/placement; systems integration/reform; child well-being indicators; research center support; needs and services for children ages 6–13; studies focused in urban areas; behavioral health treatment; building evidence on treatments and services; and juvenile justice, juvenile corrections, and juvenile probation. Foundations appear to fund areas that received fewer child welfare related grants from federal agencies. Abstract: This study identified the dollar value and research topics of federal and philanthropic grants made for child welfare research in a recent five-year period (2014–2018). More than $1 billion in child welfare research grants were identified and examined. Federal funding totaled $977 million and appeared to emphasize research related to evidence-based services and programs; child and youth behavioral health; behavioral health treatment; parent training and coaching; permanency planning and services; staff training; trauma-informed services; child developmental health; culturally competent services; case management; substance abuse treatment; birthparent services; systems reform and integration; implementation science and implementation evaluation; and adoption. Multi-state foundations funded $51 million in child welfare research, which appeared to emphasize mapping data related to child well-being; needs and services for adolescents ages 14–17 and young adults ages 18–25; independent living/transition services; education services; child and youth behavioral health; employment training/placement; systems integration/reform; child well-being indicators; research center support; needs and services for children ages 6–13; studies focused on urban areas; behavioral health treatment; building evidence on treatments and services; and juvenile justice, juvenile corrections, and juvenile probation. Foundations appear to fund areas that received fewer child welfare-related grants from federal agencies.